2013
DOI: 10.1080/02671522.2013.850528
|View full text |Cite
|
Sign up to set email alerts
|

Going ‘meta’: using a metadiscoursal approach to develop secondary students’ dialogic talk in small groups

Abstract: This paper reports on a year-long research study: four teachers of English, their Year 8 (13-14 year old) classes (110 students) in urban, secondary schools and a university teacher educator investigated the contexts for students to develop dialogic, exploratory talk in small groups. Assuming a Vygotskyan perspective, the study adapted a pedagogic model from an earlier project, endorsing a structured approach to talk, with 'ground-rules' and reflection. The study investigated how this guided model might inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 66 publications
0
9
0
2
Order By: Relevance
“…The FR + T strategies need to be embedded in teachers' practices over a longer time to make more of an impact, but this study has shown that the model tested has the potential to better support poorer readers to rapidly catch up and average + readers to be stretched. Specifically, FR + T teachers remediated students' sticking points through using the full range of comprehension strategies at the point of need in a more active ‘reading aloud’; graphic organisers supported students to understand the whole text, and seating students sociably in groups created inclusive communities of engaged and motivated readers (Oakhill et al, ; Sutherland, ). This was direct instruction in the context of a faster read of whole texts, integrated with cooperative learning, professional development and a flexible pedagogy, all four categories seen as effective in meta‐analyses of secondary reading programmes (Baye et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The FR + T strategies need to be embedded in teachers' practices over a longer time to make more of an impact, but this study has shown that the model tested has the potential to better support poorer readers to rapidly catch up and average + readers to be stretched. Specifically, FR + T teachers remediated students' sticking points through using the full range of comprehension strategies at the point of need in a more active ‘reading aloud’; graphic organisers supported students to understand the whole text, and seating students sociably in groups created inclusive communities of engaged and motivated readers (Oakhill et al, ; Sutherland, ). This was direct instruction in the context of a faster read of whole texts, integrated with cooperative learning, professional development and a flexible pedagogy, all four categories seen as effective in meta‐analyses of secondary reading programmes (Baye et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such interactive strategies are seen in studies of effective teachers of reading (Topping and Ferguson, ) and emerge from a secure, theorised knowledge base (Moats, ; Risko et al, ; Shulman, ). Additionally, reading a text aloud creates a community of readers, who produce their own situated reading practices in the classroom over time (Brown et al, ; Sutherland, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In carrying out this study, we acknowledge its potential for helping to improve practices (BAXTER, 2002;HAWORTH, 1999;Myhill, 2006;SUTHERLAND, 2015). This recognition informs the emergence of a subsidiary research question: what are the implications of researching one's teaching practice in this context?…”
Section: Bakhtin's Theories Apply To Different Registers Of the Spokementioning
confidence: 90%
“…Informed by work on the use of exploratory talk in English and other subject areas (Barnes and Todd, 1977;Mercer, 2008;Sutherland, 2013), the initial draft of the curriculum featured several collaborative activities. Informed by work on the use of exploratory talk in English and other subject areas (Barnes and Todd, 1977;Mercer, 2008;Sutherland, 2013), the initial draft of the curriculum featured several collaborative activities.…”
Section: Case Study One: English Enrichment At Whirrakee Collegementioning
confidence: 99%